2021
DOI: 10.1097/sla.0000000000004816
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Targeted Versus Standard Antibiotic Prophylaxis in Pancreatoduodenectomy in Reducing Postoperative Infectious Complications

Abstract: Introduction: Infectious complications are common after pancreatoduodenectomy, which in turn are associated with preoperative biliary drainage. Current guidelines recommend a first-generation cephalosporin as perioperative antibiotic prophylaxis. However, some studies support the use of targeted antibiotics. The aim of this systematic review and meta-analysis is to evaluate the role of prophylactic targeted antibiotics compared to standard antibiotics in reducing postoperative infections after pancreatoduodene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
(264 reference statements)
0
16
0
Order By: Relevance
“…Among the organisms that were isolated from incisional SSI, the leading isolates were Enterococcus and Enterobacter species, a result that was also in line with the findings of previous studies. 4,9,10,11,23 Generally, whether or not Enterococcus species are pathogenic for incisional SSI is dubious, 4,11 so ampicillin and vancomycin were not routinely administered as perioperative antibiotics prophylaxis when Enterococcus species were isolated from bile of PBD in this series.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Among the organisms that were isolated from incisional SSI, the leading isolates were Enterococcus and Enterobacter species, a result that was also in line with the findings of previous studies. 4,9,10,11,23 Generally, whether or not Enterococcus species are pathogenic for incisional SSI is dubious, 4,11 so ampicillin and vancomycin were not routinely administered as perioperative antibiotics prophylaxis when Enterococcus species were isolated from bile of PBD in this series.…”
Section: Discussionmentioning
confidence: 98%
“…Antibiotic prophylaxis was divided into standard and broad‐spectrum antibiotic prophylaxis. First‐ and second‐generation cephalosporins were used as standard antibiotic prophylaxis, whereas broad‐spectrum antibiotics prophylaxis included third‐ and fourth‐generation cephalosporins, cefoperazone/sulbactam, piperacillin/tazobactam, and the use of vancomycin in addition to other antibiotics 23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Controversy remains over the choice of preoperative antibiotic therapy as the effectiveness of antibiotic classes is debated, and emerging evidence suggests that institution-specific and/or targeted therapy is more effective in lowering SSI risk than any single antibiotic choice. [26][27][28][29] Intrabdominal surgery most commonly uses early-generation cephalosporins and broad-spectrum antibiotics to cover for gram-positives and/or enterococci and coliform bacteria. Moreover, coverage varies by regional resistance patterns, though antibiotic choices may be limited by patient-specific characteristics (ie, drug reactions, renal insufficiency, or liver disease).…”
Section: Discussionmentioning
confidence: 99%
“…The notion that bactibilia and resistant organisms drive postoperative SSI led to multiple retrospective series 13,14 and recently a multicenter, phase III clinical trial comparing piperacillin-tazobactam with standard-of-care cefoxitin for use as routine antibiotic prophylaxis in patients undergoing PD 15,16 . This trial demonstrated significant reduction in both SSI and CR-POPF in patients administered piperacillin-tazobactam compared with standard-of-care cefoxitin which was particularly robust in patients with preoperative biliary stents 16 .…”
mentioning
confidence: 99%